Reimagining The Internet With Edge Computing. (16th February 2021) - Varghese, Blesson; Bonomi, Flavio
Abstract: Blesson Varghese, Associate Professor in computer science at Queen's University Belfast and Flavio Bonomi, Founder of Nebbiolo Technologies and Board Technology Adviser for LYNX, explore how edge computing could foster a more ethical and fairer internet.